Diagnóstico, registro e destinação da avifauna recebida no pró-arara centro de reabilitação de animais silvestres, Araras-SP - Brito, Mônica Cristina Risso de (2017)
Brazil is considered the most diverse nation in the world and is estimated to have more than 13% of the world biota and 1919 species of birds. However, their removal from the natural environments for both illegal trade and captive maintenance, presents one of the main problems to be solved by the competent organs of fauna protection. In view of this, the centers for the rehabilitation and sorting of wild animals, responsible for receiving, identifying, marking, triaging, evaluating, recovering and allocating specimens of native wildlife were instituted. These institutions make an indispensable contribution to the process of conservation of ex situ species and are strong allies in the relocation of species in their habitat. The objective of this dissertation was to obtain data about the avifauna received at Pro-Arara, a Wildlife Rehabilitation Center created in the municipality of Araras-SP, generating information about the factors that affect the different species and motivate the delivery of these in this type of enterprise, as well as to develop a computer registry system to assist in local management. To do so, data recorded from July 2014 to July 2016 were considered for all species received and destined, as well as their provenance, analyzing by the documentation submitted by the environmental police. The development of the computer program was carried out jointly with the computer sector of the Municipality of Araras and the data collected were compiled and organized in a descriptive statistical way. During the study period, 607 birds were received, totaling 61 species distributed in 15 orders and 25 families. The most frequent order recorded was the Psittaciformes, Psittacidae family, comprising 49.59% of the total number of birds received. Within this group, individuals of the species Psittacara leucophthalmus (18,29%), Brotogeris chiriri (9,56%), Ara ararauna (7,74%) and Amazona aestiva (6,92%) predominated. Seven species are listed in the list of endangered fauna in the State of São Paulo: Ara ararauna (47), Ara chloropterus (1), Alipiopsitta xanthops (1), Sporophila maximiliani (5), Amazona amazonica (9), Sporophila angolensis (16) and Cyanoloxia brissonii (4), corresponding to 13,67% of the total. Regarding the provenance of the animals received, seizures by the environmental police (64,74%), followed by rescue of animals in situations of danger carried out by the competent organs (16,8%) predominated, and spontaneous self-surrender Population, in which the animal was in an irregular domestic guard (9,72%). Of the total number of animals received, 56,01% were referred to areas of release and monitoring in the State of São Paulo and 23,40% remained in the process of rehabilitation. The percentage of deaths recorded was 14,5%. From the results obtained, it is concluded that the Pro-Arara is a fauna enterprise with great importance for the conservation of avifauna species in the state of São Paulo and it would be important to be expanded to increase its capacity to receive animals. Another important action is the intensification of environmental education work, to raise people´s awareness in relation of the role of species in the natural environment.